The changing role of the South African intelligence community - Shaw, Mark (My University, 1995)
Intelligence – ‘spying’, in the popular imagination - operates behind an aura of great power and influence. This is particularly so in authoritarian societies, where intelligence gathering is aimed at discovering, monitoring, and acting against opponents of the regime: adjectives such as ‘hated’ and ‘feared’ cling almost automatically to intelligence agencies in this context. This was true of South Africa in the apartheid years – and beyond. At least from the time former prime minister John Vorster appointed his lifelong associate Hendrik van den Bergh to head the appropriately named Bureau of State Security (BOSS), the state's intelligence agencies were assumed to wield immense power. The impression was strengthened by allegations that intelligence services not only gathered information, but also acted in ways which flouted even the government's laws. It was they, it was assumed, who did in secret what their political masters could not order in public. For example, in the 1980s it was the chief of military intelligence, Joffel van der Westhuizen, who ordered the ‘removal from society’ of activist Matthew Goniwe....
African Studies Seminar series. Paper presented 27 March 1995
Keywords: South Africa. National Intelligence Service; Intelligence service. South Africa